Rheokinetic study on catalytic curing of oligodienurethane prepolymer with glycerol under the conditions of an excess of isocyanate groups - I. A. Novakov; D. V. Pyl’Nov; A. V. Nistratov; M. A. Vaniev; V. P. Medvedev; E. V. Petrosyan (Тонкие химические технологии)
For the first time the results of a rheokinetic study on the interaction of an oligodienuerethane prepolymer with glycerol under excessive content of isocyanate groups [NCO/OH = 1.5 (mol/mol)] are presented. It was found that, when conversion degree х ≈ 30 %, the interaction of isocyanate and hydroxyl groups is governed by the first order equation with adiabatic self-acceleration. Then (at х > 30 %) the curing process is described by the second order equation. A specific feature of the studied interactions is that, while temperature increases to 50 ° C, the role of the curing catalysts at the final stage is played by urethane and allophanate groups.